Pengaruh Penerapan Relaksasi Benson dan Aromaterapi terhadap Tingkat Nyeri pada Pasien dengan Post Operasi Appendisitis di RSAU Dr. M. Hassan Toto Tahun 2024: The Effect of Benson Relaxation and Aromatherapy on Pain Levels in Post-Appendectomy Patients at Dr. M. Hassan Toto Air Force Hospital in 2024 - Indini Putri Diningrat; Agus Purnama; Yeni Koto (Journal of Nursing Education and Practice, 2024)
Introduction: Pain experienced by post-appendectomy patients, if not properly managed, can affect the recovery period and hinder mobility following surgery. The pain problem in post-appendectomy patients can be addressed through both pharmacological and non-pharmacological interventions, such as Benson relaxation and aromatherapy. Objective: This study aims to identify the effect of Benson relaxation therapy and aromatherapy on post-appendectomy patients. Methods: This research employed an experimental design. The population consisted of pre-appendectomy patients at a general hospital (referred to as Hospital X). The sample was selected using non-random purposive sampling, with a total of 18 respondents. Results: Based on the study findings, the mean and standard deviation of pain measurements in post-appendectomy patients showed a statistically significant difference using the paired samples T-test, with a p-value of 0.001 (< 0.05) and an effect size of 7.05. This indicates that Benson relaxation and aromatherapy have a significant effect on reducing pain levels in post-appendectomy patients at Dr. M. Hassan Toto Air Force Hospital in 2024. Conclusion: There is a significant difference in pain levels before and after the application of Benson relaxation and aromatherapy in post-appendectomy patients.